Leunca (Solanum nigrum L.) Herbs Ethanolic Extract Increase Cytotoxic Activity of Cisplatin on Hela Cervical Cancer Cells - Raditya Prima Istiaji; Maya Fitria; Larasati Larasati; Fortunella Tjondro; Astrid Ayu Maruti; Erna Prawita Setyowati; Edy Meiyanto (ISCC (Indonesian Journal of Cancer Chemoprevention))
Cervical cancer is one of leading causes of cancer death in women in the developing countries. The use of cisplatin as chemotherapy agent in cervical cancer is known to cause side effects and also resistance for long-term uses. One of the strategies to prevent cervical cancer based on combination agents is being developed. Leunca (Solanum nigrum L.) has been revealed to inhibit growth of human cancer cells. Therefore, it can be used in combination with cisplatin to reduce those side effects and prevent the occurrence of cell resistance. Ethanolic extract of Leunca Herb (ELH) and cisplatin were tested their cytotoxic effect on HeLa cervical cancer cell by using MTT assay to determine IC50 value. The combinationss of cisplatin-ELH were tested to determine the combination index (CI value). The IC50 of ELH and cisplatin on HeLa cells were 227 µg/mL and 17 µM. rRespectively. Tthe study of combination resulted that almost all the index combinations were <0,9 showed the effect of synergism combination. The Ooptimum concentration of combination was 1/8 IC50 cisplatin–1/8 IC50 ELH. The results indicated that ELH had a potency to be combination agent to enhance the activity of cisplatin on HeLa cervical cancer cells. Therefore, further study on its molecular mechanism needs to be explored.